Ursachen und Therapie des Delirs - Maschke, Matthias (DMW - Deutsche Medizinische Wochenschrift, 2019)
Delirium is a potentially life-threating acute disease accompanied by a mortality up to 30 % of all affected patients. It occurs more frequently in older patients ≥ 65 years. Delirium is defined as acute onset of disturbances in attention, awareness and cognition that develops within a short period of time and fluctuates in severity. It can be subdivided in hyperactive, hypoactive and a mixed type. The hypoactive type occurs more frequently in geriatric patients and has the highest mortality of all types. Differential diagnosis of delirium include stroke, central nervous system infection, metabolic diseases, disturbances in electrolytes as well as Wernicke encephalopathy and psychiatric diseases. Treatment should be initiated rapidly and includes non-pharmacological interventions and specific pharmacological treatments. The review summarizes diagnosis and clinical management of patients with delirium.
Keywords: Delir; Delir Subtypen; hypoaktives Delir; hyperaktives Delir; postoperatives Delir